A proposed library resources and services marketing plan for the Armed Forces of the Philippines Main Library - Alunday, Wilvelyne B. (2013)
Libraries in military camps need to market their resources and services not just to military personnel but also to the civilian residents. This study focused on the improvement of the current marketing efforts of the Armed Forces of the Philippines Main Library (AFPML) and on the awareness of the civilians and military personnel residents inside Camp General Emilio Aguinaldo about the AFPML's library resources and services.